Under the skin: does psychiatric outcome of bullying victimization in school persist over time? A prospective intervention study - Jantzer, Vanessa; Ossa, Fanny; Eppelmann, Lena; Parzer, Peter; Resch, Franz; Kaess, Michael (The journal of child psychology and psychiatry, 2022)
Background Research has shown a direct path between peer victimization and poor mental health outcomes. However, the impact of bullying prevention on mental health is a largely unexplored field. Therefore, our study examined the longitudinal association between bullying development and trajectories of psychiatric symptoms (emotional problems, total difficulties, nonsuicidal self-injury, and suicidality) and health-related quality of life (HRQL) during the implementation of school-based bullying prevention. Methods Data of 4,873 pupils (grades 5-13) were collected in 23 schools implementing the Olweus Bullying Prevention Program (OBPP). Self-report questionnaires were administered at three annual assessment waves and individual codes enabled the association of repeated assessments to the same pupil. Latent growth curve models (LGCMs) were used to examine the relation among bullying status and mental health outcome with mixed-effects linear regressions estimating the association of changes in bullying with changes in continuous scores and mixed-effects logistic regressions for categorical variables. Results Latent growth curve models revealed an improvement of mental health and HRQL through the termination of bullying for every outcome variable of interest (all p < .001). Correspondingly, we found an explicit increase in psychopathology as well as decrease in HRQL within one year as a result of developing victimization (all p < .001). Interestingly, the growth of psychopathology associated with the onset of bullying was significantly steeper than its decline associated with the termination of bullying. The postulated cumulative effect of ongoing bullying for a further year could only be shown for HRQL (p = .025) and total difficulties (p = .034), but not for specific mental health problems (all p > .117). Conclusions Latent growth curve models clearly showed that the adverse psychosocial consequences of bullying arise quickly but seem to reduce much slower and partly persist over time. Future long-term studies are necessary to clarify if mental health problems will return to baseline after several years or if residual symptoms will remain.
First published: 16 August 2021
Gesehen am 14.08.2023